2013
DOI: 10.1538/expanim.62.63
|View full text |Cite
|
Sign up to set email alerts
|

A Rat Model of Intracerebral Hemorrhage Permitting Hematoma Aspiration plus Intralesional Injection

Abstract: A combination of hematoma aspiration and local delivery of chemicals may be more effective than either therapy in intracerebral hemorrhage (ICH). The aim of the present study was to develop a rat model of hematoma aspiration plus intralesional injection after ICH. ICH was induced in adult Sprague-Dawley rats by an intrastriatal injection of bacterial collagenase IV. Hematoma aspiration was performed 3.5 h after ICH onset. Following aspiration, normal saline was injected into the lesion cavity. Hematoma aspirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Our previous study showed that hypertension aggravated ICH-related brain injury and deficits in the rat [12]. Moreover, stereotactic aspiration of blood led to decompression of brain tissue in these normotensive rats [13]. In the present study, the RADA16-I SAP solution could fill in brain cavity created by hematoma aspiration and, more importantly, it could stop hematoma growth in the hypertensive rats.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Our previous study showed that hypertension aggravated ICH-related brain injury and deficits in the rat [12]. Moreover, stereotactic aspiration of blood led to decompression of brain tissue in these normotensive rats [13]. In the present study, the RADA16-I SAP solution could fill in brain cavity created by hematoma aspiration and, more importantly, it could stop hematoma growth in the hypertensive rats.…”
Section: Discussionsupporting
confidence: 49%
“…RVHT was induced by applying a silver clip to the left renal artery [13]. Six weeks after renal artery constriction, hypertensive rats were randomly assigned to one of the four groups: the ICH only group, with induction of ICH and sham hematoma aspiration; the aspiration only (Asp) group, with induction of ICH and subsequent hematoma aspiration; the saline group, with induction of ICH, hematoma aspiration, and intralesional injection of saline; and the SAP group, with induction of ICH, hematoma aspiration, and intralesional injection of the SAP solution.…”
Section: Methodsmentioning
confidence: 99%
“…Research has suggested that early removal of the hematoma by MIHA could reduce the expansion of the hematoma, the production of inflammatory mediator, and the direct chemical damage to brain tissue [ 10 ]. However, the research on the relationship between MIHA and JNK pathway has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The experiments were carried out on 7 white outbred male rats weighing 250-400 g, aged 11-13 months. All animals underwent surgery to simulate ICH [5]. To perform the surgery, the rats were anesthetized by intraperitoneal injection of 15 mg/kg propofol (Daewon Pharmaceutical Co. Ltd. Korea/Switzerland) and 5 mg/kg xylazine (Biowet Puławy Sp., Poland).…”
Section: Intracerebral Hemorrhage Modelingmentioning
confidence: 99%